Enhanced thermoelectric cooling properties of Bi2Te3−xSex alloys fabricated by combining casting, milling and spark plasma sintering. (November 2016) - Han, Seung Tek; Rimal, Pradip; Lee, Chul Hee; Kim, Hyo-Seob; Sohn, Yongho; Hong, Soon-Jik
Abstract: Bi2 Te3−x Sex alloys are extensively used for thermoelectric cooling around room temperature, but, previous studies have reported peak thermoelectric efficiency of the material at higher temperature around 450 K. This study presents the casting followed by high energy ball milling and spark plasma sintering as a thriving methodology to produce efficient and well-built Bi2 Te3−x Sex material for the thermoelectric cooling around room temperature. In addition, changes in electrical and thermal transport properties brought up by amount of Se in the Bi2 Te3−x Sex material for this methodology are measured and discussed. Although Seebeck coefficient and electrical conductivity showed irregular trend, power factor, thermal conductivity and figure of merit ZT gradually decreased with the increase in amount of Se. A maximum ZT value of 0.875 at 323 K was obtained for x = 0.15 sample owing to its higher power factor. This value is 17% and 38% greater than for x = 0.3 and x = 0.6 samples respectively. At 323 K, herein reported ZT value of 0.875 is higher than the state of art n-type Bi2 Te3 based thermoelectric materials produced by the time consuming and expensive methodologies. Graphical abstract: Highlights: Efficient thermoelectric materials are fabricated at low cost and shorter time. Bi2 Te3−x Sex alloys are produced by combining casting and high energy ball milling. Amount of x neither influences powder morphology nor bulk microstructure. Increase in x decreases power factor, thermal conductivity and figure of merit ZT. Bi2 Te2.85 Se0.15 alloy exhibits ZT higher than state of art n-type materials at 323 K.